2008
DOI: 10.1002/lt.21495
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative dobutamine stress echocardiographic findings and subsequent short-term adverse cardiac events after orthotopic liver transplantation

Abstract: Cardiovascular (CV) complications are the leading cause of non-graft-related death in orthotopic liver transplant (OLT) patients. Pretransplant cardiac evaluation using dobutamine stress echocardiography (DSE) is commonly utilized for risk stratification of OLT candidates. To determine if clinical and echocardiographic variables identify patients with increased CV risk, we performed a retrospective chart review of all 284 patients that underwent OLT at our institution between June 1999 and August 2005. Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 28 publications
(36 reference statements)
4
88
2
2
Order By: Relevance
“…In a review of 157 pre-transplant dobutamine stress echocardiographys (DSEs), Umphrey et al [50] found 37% to be inconclusive due to failure to reach 85% of their maximum predicted heart rate.…”
Section: Systolic Incompetencementioning
confidence: 99%
“…In a review of 157 pre-transplant dobutamine stress echocardiographys (DSEs), Umphrey et al [50] found 37% to be inconclusive due to failure to reach 85% of their maximum predicted heart rate.…”
Section: Systolic Incompetencementioning
confidence: 99%
“…[20][21][22] Earlier studies evaluating the DSE as a screening technique for obstructive coronary artery disease in ESLD patients have yielded conflicting results. [7][8][9][10][11] Plotkin and associates concluded that the DSE has sensitivity, specificity, and positive and negative predictive values of 100% 9 ; however, Harinstein and associates reported that the DSE has a poor sensitivity as a screening test for obstructive coronary artery disease in LT candidates and recommend alternate or additional methods for adequate cardiac risk stratification. 2,8 limitations This is a retrospective study based on chart reviews and has a low event rate; therefore, drawing statistical conclusions may be difficult.…”
Section: Model Of End-stage Liver Disease Score and Chronotropic Incomentioning
confidence: 99%
“…Although various studies have produced conflicting results about the predictive value of DSE in these patients. [7][8][9][10][11] This study sought to determine the prevalence and causes of chronotropic incompetence in patients with ESLD, and to examine the adequacy of our current DSE protocol in predicting cardiac events after an LT.…”
Section: Introductionmentioning
confidence: 99%
“…However there has been demonstrated a high negative predictive value of this test. (Umphrey et al 2008). …”
Section: The Role Of Doppler Echocardiography During Liver Transplantmentioning
confidence: 99%